Parental Involvement in Secondary School Curriculum Implementation: The Case of East Wollega Zone, Ethiopia - Tuli, Dereje Mengistu; Tarekegne, Wudu Melese (Journal of Education and Research, 2019)
This study assesses the practices of parental involvement in curriculum implementation in East Wollega Zone in Ethiopia. To this end, a cross-sectional survey was designed. The data were collected from randomly selected teachers, students, Parent-Teacher Association (PTA) members, school principals, parents and supervisors through questionnaires and interview. Then, the quantitative data were analyzed and interpreted through frequency and mean score and the qualitative data were coded and narrated thematically. The findings indicated that the involvement of parents in general secondary schools curriculum implementation in East Wollega Zone was found to be low. However, efforts of the PTAs in having parents for planning and decision-making of curriculum implementation was high. The major challenges were inadequate school facility, inadequate training, parent’s lack of awareness, lack of good governance, and the unwillingness of teachers. To increase parental involvement, general secondary schools, woreda and zone education offices may train stakeholders, allocate adequate budget and schools should design an income-generating mechanism to fulfil school facilities and making parents active in curriculum implementation.